Perspectives on the training and education of world class engineers - Gopez, Adolfo Jesus R.
World class manufacturing implies a philosophy of manufacturing excellence. It is strongly dependent on having properly trained engineers. It is also strongly linked to the ability of a company to compete in the global market. Using Michael E. Porter's "The Competitive Advantage of Nations" as the framework together with the increasingly strict requirements of the semiconductor industry as a benchmark, this paper presents viewpoints on the training of engineers for global competitiveness. Experiences drawn from the UP and DLSU Manufacturing Linkage Programs were also used for guidance. The critical items required for engineers to be competitive in a world class environment include : the ability to solve problems by proceeding from the basics and the ability to consider the human aspects as part of a technician solution. Additional technical aspects would be based on Total Quality Management (TQM), together with additional training on statistical concepts applied to process improvement, manufacturing and design of experiments. Finally, the training must emphasize innovativeness and even creativity.